2005
DOI: 10.1093/fampra/cmi075
|View full text |Cite
|
Sign up to set email alerts
|

Screening for domestic violence in a predominantly Hispanic clinical setting

Abstract: HITS demonstrated good reliability and validity with ISA-P in English speaking patients. The Spanish version of HITS showed moderate reliability and good validity with WAST in Spanish speaking patients. HITS may help physicians detect abuse in predominantly Hispanic clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 24 publications
1
81
1
1
Order By: Relevance
“…The HITS screening tool 13 comprises the following four items: "Over the last 12 months, how often did your partner: (1) physically hurt you, (2) insult you or talk down to you, (3) threaten you with harm, and (4) scream or curse at you?" Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Findings support the concurrent validity of this instrument.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…The HITS screening tool 13 comprises the following four items: "Over the last 12 months, how often did your partner: (1) physically hurt you, (2) insult you or talk down to you, (3) threaten you with harm, and (4) scream or curse at you?" Responses are scored on a 5-point scale from 1 ("never") to 5 ("frequently") and summed for a total score (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Findings support the concurrent validity of this instrument.…”
Section: Methodsmentioning
confidence: 91%
“…Findings support the concurrent validity of this instrument. 13,15,16 In addition, support for the reliability, sensitivity, and specificity of this instrument has been provided in several studies, although results vary with regard to the most appropriate cutoff score identified for different samples. Specifically, while findings from a sample of general female primary care patients were compared with a sample of women who were currently seeking help for IPV indicate that a cutoff score of 11 has a sensitivity of 96 % and specificity of 91 % in detecting IPV victims, 13 other studies have supported a lower cutoff score of 6 in some diverse populations, including ethnic minority women.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cross-sectional study, [10] tested the reliability and validity of a brief 4-question instrument, the Hurt Insult Threaten Scream (HITS) among predominantly Hispanic women. Two hundred and two women completed the HITS and two other previously validated tools, the Index of Spouse Abuse-Physical Scale (ISA-P) and the Woman Abuse Screening Tool (WAST).…”
Section: Measure Of Construct: B: (Socio-economic)mentioning
confidence: 99%